Circuits regulating pleasure and happiness in major depression. (February 2016) - Loonen, A.J.M.; Ivanova, S.A.
Abstract: The introduction of selective serotonin reuptake inhibitors has gradually changed the borders of the major depression disease class. Anhedonia was considered a cardinal symptom of endogenous depression, but the potential of selective serotonin reuptake inhibitors to treat anxiety disorders has increased the relevance of stress-induced morbidity. This shift has led to an important heterogeneity of current major depressive disorder. The complexity can be disentangled by postulating the existence of two different but mutually interacting neuronal circuits regulating the intensity of anhedonia (lack of pleasure) and dysphoria (lack of happiness). These circuits are functionally dominated by partly closed limbic (regulating misery-fleeing behaviour) and extrapyramidal (regulating reward-seeking behaviour) cortico-striato-thalamo-cortical (CSTC) circuits. The re-entry circuits include the shell and core parts of the accumbens nucleus, respectively. Pleasure can be considered to result from finding relief from the hypermotivation to exhibit rewarding behaviour, and happiness from finding relief from negative or conflicting circumstances. Hyperactivity of the extrapyramidal CSTC circuit results in craving, whereas hyperactivity of the limbic system results in dysphoria.